Standards for Quality of Supervisors of Examiners Selecting for Masters Thesis in Education Faculties of Gazza Universities from Their Points of View - Mohammad Ibrahim (University of Science and Technology, Yemen, 2013)
Abstract The present study aimed at identifying quality standards in the selection of supervisors and examiners for theses in colleges of education in the Palestinian universities in the Gaza Strip from their point of view. The study sample consisted of (68) supervisors and the teaching staff of the Palestinian universities in the Gaza Strip. A list of criteria is prepared consisting of ( 24) items distributed on four areas: supervisor and his  educational qualifications, examiners and their educational qualifications, panels of discussion and reviewing and the role of Graduate Studies in the supervision of theses. The results showed that the area of the formation of panels of discussion and reviewing came in first place with a percentage of (69.95), the field of the supervisor and his educational qualifications came in the second place with a percentage of (69.33), of the role of graduate studies in the supervision of the theses came in third place with a percentage of (69.31),and, then,examiners and their educational qualificationscame in the finalrank with a percentage of   (66.53). The  results of the study showed that there were no differences of  statistical significance s (0.05) in the degree of availability of quality standards due to the variables of the study such as university, experience in supervision and reviewing , while there are differences to the variable of degree qualification  of Assistant Professor and Professor in favor of the professor.The study recommended the need to work on applying quality standards in the appointment of the supervisors of the theses in education and in the formation of panelsof discussion and reviewing.   Key words: quality, quality criteria, Graduate Studies, supervisor, discussion panels and reviewing.